Influence of Carbon Emission Disclosure, Green Innovation, and Media Exposure on Firm Value - Novia Anggraeni; Fitriyah Fitriyah (CV. Proaksara Global Transeduka, 2025)
The objective of this research is to investigate how publicizing carbon emissions, implementing eco-friendly innovations, and gaining media coverage can impact the overall worth of a company. The study involved an examination of yearly reports, sustainability reports, and company websites belonging to energy sector businesses trading on the Indonesia Stock Exchange from 2019 to 2023. This research examined 16 energy sector companies listed on the Indonesia Stock Exchange between 2019 and 2023, using a purposive sampling method. The study relied on secondary data, including annual reports, sustainability reports, and the official websites of the selected companies. This study utilizes several variables, including Carbon Emissions Disclosure (X1) as the first independent variable, Green Innovation (X2) as the second independent variable, and Media Exposure (X3) as the third independent variable. Meanwhile, Firm Value (Y) serves as the dependent variable. In this study, the research methodology involves utilizing panel data regression. EViews 12 Student Version Lite software is employed to analyze the research findings. It was determined that the Common Effect Model (CEM) performed the best among all the models evaluated. The findings of this study reveal that Carbon Emissions Disclosure, when considered individually, does not influence Firm Value. Green Innovation, on the other hand, has a partial effect on Firm Value, while Media Exposure shows no partial impact. However, when analyzed simultaneously, Carbon Emissions Disclosure, Green Innovation, and Media Exposure collectively influence Firm Value.